Tanggngjawab Pidana Pelaksanaan Penyidikan Tindak Pidana Cukai Rokok Atas Pelanggaran Cukai Rokok Ilegal Berdasarkan Undang-Undang Nomor 39 Tahun 2007 - Deddy Afdhal; Ramlani Lina Sinaulan; Mohamad Ismed (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Discussion on criminal responsibility for conducting investigations into criminal acts of cigarette excise on illegal cigarette excise violations based on Law No. 39 OF 2007. The approach method used in this legal research is a normative juridical approach which is supported by empirical juridical by detailing the description, namely research that Deductive analysis begins with an analysis of the articles in the laws and regulations governing the issue of conducting investigations into criminal acts of cigarette excise on illegal cigarettes based on Law number 39 of 2007 and legal responsibility for perpetrators of excise crimes for the implementation of law number 39 of 2007. The executor in the field of excise is the Directorate General of Customs and Excise so that the enforcement of the Excise Law is carried out by the ranks of the Directorate General of Customs and Excise, both from the central level and the level of service and supervision in the smallest units in the region. The enforcement of the Excise Law by the Directorate General of Customs and Excise is carried out through two types of sanctions, namely administrative sanctions and criminal sanctions.Keywords: Criminal Liability; Cigarette Excise Violation Abstrak Pembahasan mengenai Tanggungjawab pidana pelaksanaan penyidikan tindak pidana cukai rokok atas pelanggaran Cukai rokok ilegal berdasarkan Undang-undang nomor 39 TAHUN 2007. Metode pendekatan yang dipergunakan dalam penelitian hukum ini adalah metode pendekatan yuridis normatif yang  didukung  dengan  yuridis empiris dengan merinci uraian  yaitu suatu penelitian yang secara deduktif dimulai analisa terhadap pasal-pasal dalam peraturan perundang-undangan yang mengatur terhadap permasalahan Pelaksanaan penyidikan tindak pidana cukai rokok atas rokok ilegal berdasarkan Undang-undang nomor 39 tahun 2007 dan Tanggungjawab hukum atas pelaku tindak pidana cukai atas pelaksanaan undang-undang nomor 39 tahun 2007. Pelaksana dibidang cukai adalah Direktorat Jenderal Bea dan Cukai sehingga penegakan Undang-Undang Cukai dilakukan oleh jajaran Diretorat Jenderal Bea dan Cukai, baik dari tingkat pusat maupun tingkat pelayanan dan pengawasan di unit terkecil di daerah. Penegakan Undang-Undang Cukai oleh Direktorat Jenderal Bea dan Cukai dilakukan melalui dua jenis pengenaan sanksi, yaitu sanksi administrasi dan sanksi pidana.Kata Kunci:  Tanggungjawab Pidana; Pelanggaran Cukai Rokok; Tindak Pidana  Cukai